Measurement of fiber non-linearity based on four-wave mixing with an ASE source - Kharraz, O.M.; Mohammad, A.B.B.; Forsyth, D.I.; Ahmad, Harith (Elsevier, 2016)
A new four-wave mixing scheme to practically measure the non-linear coefficient of fibers is introduced. A single erbium-doped fiber amplifier is used to create the two wavelengths for the four-wave mixing inputs, which are pre-spectrally sliced via fiber Bragg grating filters. The proposed scheme avoids the Brillouin backscattering, rendering this a more accurate method to determine fiber nonlinearities than conventional coherent FWM systems. Furthermore, the generated FWM seed beams are pure and ultra-narrow, and can therefore be treated as coherent light. Consequently, accurate degeneracy factor can also be taken into consideration.